Development of Magnetic Functional Materials Based on Carbon/Manganite/Ferrite Composites for Microwave Absorber Materials Applications: Maya Puspitasari Izaak, Yohanes Edi Gunanto, Henni Sitompul, Wisnu Ari Adi - Maya Puspitasari Izaak Maya Puspitasari Izaak; Yohanes Edi Gunanto Yohanes Edi Gunanto; Henni Sitompul Henni Sitompul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2021)
The synthesis of carbon/manganite/ferrite composite materials for microwave absorber applications has been successfully carried out with variations in the composition of 15:55:30 and 15:45:40 (wt%). This composition was successfully confirmed based on the analysis of the X-ray diffraction pattern using the GSAS program. The refinement results show that each phase of each composite has a good structure. Based on surface morphological observations, it is known that the composite samples have varying particle sizes of around 150-500 nm which are evenly distributed over the entire surface of the sample. The result of the microwave absorption analysis implies that the difference in composition results in a slight increase of the reflection loss and the presence of a new absorption peak at a frequency of 4.36 GHz. Our result underlines that the characteristic of microwave absorption in composites is insignificantly influenced by the composition of the material as the absorption properties are mainly affected by the respective phases that form it, not by the entire phase of the composite.